Pore forming method and application of modified porous hard carbon negative electrode material without protective gas
Through the pore-making method of modified porous hard carbon negative electrode material without protective gas, the problem of sodium ion migration in the prior art is solved in the process of high-rate charging and discharge of porous hard carbon materials, which is effective in improving pore-making and material performance, and is suitable for low-cost industrial production.
Patent Information
- Application Number
- CN202411831987.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-04
AI Technical Summary
The porous hard carbon of the negative electrode material of existing sodium ion battery is prone to form invalid pores during the high-rate charging and discharging process or some sites cannot form pores, resulting in the migration of sodium ions being blocked, and the use of protective gases leads to waste of resources, which is not conducive to low-cost industrial production.
The pore-making method of modified porous hard carbon negative electrode material without protective gas is adopted. The biomass raw materials are pre-calcined under oxygen-free and negative pressure conditions, combined with epoxy resin and starch substances, and ball milling is used to mix with sodium hydroxide solution, and the modified porous hard carbon negative electrode material is formed by spray drying and ultra-high temperature calcination.
It realizes efficient pore making without protective gas, improves the conductivity, reversible capacity and cycle stability of the material, and significantly improves the rate performance and first-time Coulomb efficiency of the sodium ion battery.
Smart Images

Figure CN119750540A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for sodium ion batteries, and in particular to a pore-forming method and application of a modified porous hard carbon negative electrode material that does not require protective gas. Background Art
[0002] As the global demand for clean and sustainable alternative energy continues to increase, efficient energy storage technology has become particularly important. As the current mainstream energy storage technology, lithium-ion batteries have been widely used in electric vehicles, smart grids, and portable electronic devices. However, with the continuous expansion of the lithium-ion battery market, the demand for lithium resources is also increasing sharply, resulting in tight supply of lithium resources and rising prices. Therefore, the development of new, low-cost, high-performance energy storage technologies has become a hot topic in current research.
[0003] As a potential alternative to lithium-ion batteries, sodium-ion batteries have attracted much attention due to their abundant sodium resource reserves, low cost and similar working principles. The research and development of key components such as positive and negative electrode materials and electrolytes of sodium-ion batteries has become an important research direction in the current field of sodium-ion batteries. Among them, porous hard carbon has become an ideal choice for negative electrode materials of sodium-ion batteries due to its high specific surface area, rich pore structure, good conductivity and high chemical stability. Porous hard carbon can bind more sodium ions, providing high capacity for sodium-ion batteries, while also having good cycle stability and rate performance.
[0004] The existing palm hard carbon directly fired materials are prone to form a large number of invalid open pores, or some sites cannot form pores, which greatly reduces the sodium storage sites, hindering the migration of sodium ions during high-rate charge and discharge. After the accumulation of dendrites at the negative electrode, it will cause the diaphragm to contact the positive electrode, thus forming a closed-loop circuit and causing a short circuit. In addition, the use of protective gas will greatly waste resources and is not conducive to low-cost industrial production.
[0005] Based on the above reasons, this application is filed. Summary of the invention
[0006] Based on the above reasons, in response to the problems or defects existing in the prior art, the purpose of the present invention is to provide a pore-forming method and application of modified porous hard carbon negative electrode materials without the need for protective gas, so as to solve or at least partially solve the above-mentioned technical defects existing in the prior art.
[0007] In order to achieve the above first object of the present invention, the technical solution adopted by the present invention is as follows:
[0008] A method for forming pores in a modified porous hard carbon negative electrode material without the need for protective gas, the method specifically comprising the following steps:
[0009] (1) pre-calcining the biomass raw material under oxygen-free and negative pressure conditions to obtain a hard carbon precursor; after crushing, acid washing and water washing to neutrality to obtain a purified hard carbon precursor dispersion;
[0010] (2) adding epoxy resin and starch material to the purified hard carbon precursor dispersion in order according to the ratio, mixing, and obtaining a mixed slurry A; then adding sodium hydroxide solution to the mixed slurry A according to the ratio, stirring for 1-3 hours, obtaining a mixed slurry B, and mixing by ball milling to form a mixed material;
[0011] (3) spray drying the mixture, and then calcining it at 1050-1700° C. for 2-4 hours; after the calcination, cooling the obtained product to room temperature to obtain the modified porous hard carbon negative electrode material.
[0012] Specifically, in some embodiments of the present invention, the anaerobic condition in step (1) is achieved by using a vacuum filter to extract the air to below 0.01 Pa.
[0013] Specifically, in the above technical solution, a negative pressure environment is used in step (1) because the tar produced by the reaction needs to be separated from the material system.
[0014] Furthermore, in the above technical solution, the biomass raw material in step (1) can be one or more of palm, bamboo, hard fruit shell, straw, grass leaves, etc.
[0015] Furthermore, in the above technical solution, the pre-calcination temperature in step (1) is 600-800° C., and the pre-calcination treatment time is 3-5 hours, preferably 4 hours.
[0016] Furthermore, in the above technical solution, the mass ratio of the hard carbon precursor to the epoxy resin in step (2) is 100:1-8.
[0017] Furthermore, in the above technical solution, the starch material in step (2) is a mixture of one or more of corn starch, potato starch, rice starch, wheat starch, etc.
[0018] Furthermore, in the above technical solution, the mass ratio of the hard carbon precursor to the starch material in step (2) is 100:8-26.
[0019] Furthermore, in the above technical solution, the mass ratio of the hard carbon precursor to the sodium hydroxide in the sodium hydroxide solution in step (2) is 100:22-43.
[0020] Furthermore, in the above technical solution, the mass fraction of the sodium hydroxide solution in step (2) is 20-30%. In a preferred embodiment of the present invention, the mass fraction of the sodium hydroxide solution is 25%.
[0021] Furthermore, in the above technical solution, the sodium hydroxide solution in step (2) is prepared by dissolving sodium hydroxide in deionized water and mixing the mixture.
[0022] Furthermore, in some embodiments of the present invention, the specific process of the spray drying in step (3) is as follows: the spray drying inlet air temperature is adjusted to 160 degrees Celsius, the outlet air temperature is adjusted to 100 degrees Celsius, and the rotation speed is adjusted to 2000 cycles per minute.
[0023] The second object of the present invention is to provide a modified porous hard carbon negative electrode material prepared by the above-mentioned method.
[0024] The third object of the present invention is to provide an application of the modified porous hard carbon negative electrode material prepared by the above method in sodium ion batteries.
[0025] The fourth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein: the active material used in the negative electrode is the modified porous hard carbon negative electrode material prepared by the above-mentioned method.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The epoxy resin in the present invention acts as a binder, which plays a vital role in the hard carbon firing process: it can firmly combine the hard carbon particles together to form a stable structure, and fuse with the carbon source in the starch material. The binder can also maintain a certain stability at high temperature to prevent the hard carbon material from deforming or breaking during the firing process. After treatment, a semi-finished product of a resin-coated hard carbon precursor with nanocarbon is formed. This biomass-based sodium ion battery hard carbon negative electrode material is obtained by coating the precursor with epoxy resin cracking carbon, and the cracked carbon is evenly attached to the periphery of the carbonized material through the adhesiveness of the resin. In the later heat treatment process of the carbonized material, a layered structure coated with resin cracking carbon is formed, which effectively improves the conductivity and reversible capacity of the material.
[0028] (2) The main reason for selecting sodium hydroxide in the present invention is that it undergoes an oxidation-reduction reaction with hard carbon at high temperature to generate products such as metallic sodium, carbon dioxide and water vapor. These products will leave pores inside the hard carbon during the escape process. Sodium hydroxide, as a pore-forming agent, mainly forms pores inside the hard carbon through physical effects such as penetration and expansion. The size and distribution of these pores depend on factors such as the type and concentration of the molten salt and the calcination conditions.
[0029] (3) The present invention is conducive to constructing a stable skeleton structure during the charge and discharge process through spray drying, further improving the cycle stability of the material, providing more channels for the rapid insertion and extraction of sodium ions, and is conducive to improving the high current discharge capacity of the material.
[0030] (4) The present invention uses the best ratio of raw materials combined with different firing temperatures and firing times to increase the voids, and innovatively does not use protective gas for ultra-high temperature calcination.
[0031] (5) The present invention forms pores in biomass materials by mixing and doping different materials, which can form a large number of effective closed pores, effectively inhibit capacity attenuation, and improve the rate performance of the material. The porosity limit of chemical etching is improved, and the porous structure can significantly increase the specific surface area ratio of the hard carbon material, thereby increasing its adsorption capacity, catalytic activity, and electrochemical performance. At the same time, the first calcination is carried out at a lower temperature to construct a stable structure with a smaller specific surface area, thereby improving the battery performance such as the first coulomb efficiency, specific capacity, and cycle stability. Then, the second calcination is carried out under an inert atmosphere and high temperature to form a stable carbon phase structure, which is beneficial to inhibit the volume expansion of the sodium ion battery and improve the cycle stability. The porous hard carbon negative electrode material prepared by the present invention has a high specific capacity, a high first coulomb efficiency, and has excellent rate performance and cycle stability. Experiments show that the first cycle charging specific capacity of the palm hard carbon negative electrode material with multiple types of carbon sources of the present invention reaches 353mAhg -1 The first coulombic efficiency is 94.79%; after 500 cycles, the capacity is 294.2 mAh g -1 , the Coulombic efficiency is about 100%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 XRD comparison diagrams of modified porous hard carbon negative electrode materials JH-1 and JH-2 prepared in Example 1 and Comparative Example 1 of the present invention, respectively;
[0034] Figure 2 (a) and (b) are scanning electron microscope (SEM) images of the modified porous hard carbon negative electrode materials JH-1 and JH-2 prepared in Example 1 and Comparative Example 1 of the present invention, respectively;
[0035] Figure 3It is a comparison chart of the first cycle discharge capacity of button cells using the modified porous hard carbon negative electrode materials JH-1 and JH-2 prepared in Example 1 of the present invention and Comparative Example 1 respectively as negative electrode active materials. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.
[0037] According to the information contained in this application, various changes can be easily made to the precise description of the present invention for those skilled in the art.It should be understood that the scope of the present invention is not limited to defined processes, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention.
[0038] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.
[0039] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0040] Example 1
[0041] The present embodiment provides a method for forming pores in a modified porous hard carbon negative electrode material (JH-1) without the need for protective gas, and the method specifically comprises the following steps:
[0042] 1. Pre-calcination: Select palm as raw material, place it in a box furnace, use a suction filter to extract the air in the furnace to below 0.01pa, and pre-calcine the palm in an oxygen-free environment under negative pressure conditions: start heating from room temperature, step by step increase of 0.5 degrees Celsius per minute to 650 degrees Celsius and keep it warm for 4 hours until the oxygen content in the palm oil residue does not exceed 6%, and then start cooling down to 25 degrees Celsius at a rate of 0.5 degrees Celsius per hour to obtain a pre-carbonized material;
[0043] 2. Crushing: crushing the pre-carbonized material to obtain a hard carbon precursor powder with a size of less than 50 microns;
[0044] 3. Pickling: adding the hard carbon precursor powder into 4% by mass dilute hydrochloric acid, stirring and cleaning;
[0045] 4. Purification: adding the hard carbon precursor after acid washing in step 3 into deionized water, stirring and washing for multiple times until the washing liquid is neutral, to obtain a purified hard carbon precursor dispersion;
[0046] 5. Weighing 5% of the mass of the hard carbon precursor powder, epoxy resin is added to the purified hard carbon precursor dispersion and mixed;
[0047] 6. Weigh corn starch according to 15% of the mass of the hard carbon precursor powder, add it to the mixed slurry obtained in step 5, mix well, and obtain mixed slurry A; then add sodium hydroxide solution with a mass fraction of 25% to the mixed slurry A to obtain mixed slurry B; wherein: the mass ratio of the hard carbon precursor to the sodium hydroxide in the sodium hydroxide solution is 100:22.
[0048] 7. Ball-mill the mixed slurry B to form a mixed material.
[0049] 8. Spray drying: The specific process of the spray drying is as follows: the spray drying inlet air temperature is adjusted to 160 degrees Celsius, the outlet air temperature is adjusted to 100 degrees Celsius, and the rotation speed is adjusted to 2000 cycles per minute.
[0050] 9. Calcination: The spray-dried semi-finished product is heated to 1250 degrees Celsius and calcined for 2 hours in an oxygen-free negative pressure environment; the heating rate is: 4 degrees Celsius per hour, and the temperature is increased in a step-by-step manner; after the calcination, the resulting product is cooled to room temperature at a temperature of 4 degrees Celsius per hour to obtain the modified porous palm hard carbon negative electrode material.
[0051] Example 2
[0052] The method of forming pores in a modified porous hard carbon negative electrode material without protective gas in this embodiment is basically the same as that in Example 1, except that the calcination temperature in the ninth step in Example 1 is changed to 1500 degrees Celsius in this embodiment.
[0053] Example 3
[0054] The method of forming pores in a modified porous hard carbon negative electrode material without protective gas in this embodiment is basically the same as that in Example 1, with the only difference being that the calcination time in the ninth step of Example 1 is changed to 4 hours in this embodiment.
[0055] Example 4
[0056] The method of forming pores in a modified porous hard carbon negative electrode material without protective gas in this embodiment is basically the same as that in Example 1, with the only difference being that the temperature increase during calcination in the ninth step in Example 1 is changed to 10 degrees Celsius per hour.
[0057] Comparative Example 1
[0058] This comparative example provides a method for forming pores in a modified porous hard carbon negative electrode material (JH-2) that does not require protective gas. The method is basically the same as Example 1, with the only difference being that this comparative example does not use sodium hydroxide solution during the modification process, and the remaining steps are the same.
[0059] Table 1 compares the electrochemical performances of batteries assembled using the modified porous hard carbon negative electrode materials prepared in Examples 1-4 and Comparative Example 1, respectively, as negative electrode active materials. In addition, Table 1 also lists the specific surface areas of the modified porous hard carbon negative electrode materials prepared in Examples 1-4. It can be seen from this summary table that Example 2 is the most advantageous preparation condition for preparing the modified porous hard carbon negative electrode material of the present invention.
[0060] Table 1d
[0061] serial number <![CDATA[Specific surface area of material (m 2 / g)]]> Battery discharge first-effect specific capacity (mAh) Battery charging first effective specific capacity (mAh) Battery cycle number (weeks) Example 1 1992.98 353 312 5000 Example 2 1181.12 274 232 3800 Example 3 1003.13 353 312 5000 Example 4 750.67 180 276 4000 Comparative Example 1 452.42 150 94 4000
[0062] As can be seen from Table 1, the invention uses the best proportion of raw materials and the best firing temperature is 1250 degrees Celsius, which is Example 1. When the firing temperature is 1500 degrees Celsius (Example 2), part of the material will be graphitized, resulting in a decrease in capacity. The insulation time is suitable for 2 hours to 4 hours, which does not affect the material properties. Too fast a heating rate will affect the pore size shrinkage and reduce the hard carbon specific surface area, thereby affecting the capacity, which is Example 4. It can be seen from the comparative example that the use of sodium hydroxide solution can greatly increase the capacity.
[0063] Figure 1 XRD comparison diagrams of modified porous hard carbon negative electrode materials JH-1 and JH-2 prepared in Example 1 and Comparative Example 1, respectively. It can be seen from the XRD diagram that the process can prepare hard carbon materials. However, the prominent peak of JH-2 is low, proving that when θ is 100°, some carbon materials have not formed the lattice required for hard carbon.
[0064] Figure 2 (a) and (b) are scanning electron microscope (SEM) images of the modified porous hard carbon negative electrode materials JH-1 and JH-2 prepared in Example 1 and Comparative Example 1 of the present invention, respectively. From the microstructure, we can see that there are many etched parts on the surface of JH-1, and there are fewer etched parts on the surface of JH-2. The larger the specific surface area, the stronger the sodium storage capacity, and the larger the structural container of the hard carbon. JH-1 has a large specific surface area, many sodium storage sites, and a strong capacity.
[0065] The modified porous hard carbon negative electrode materials prepared in the above Example 1 and Comparative Example 1 were used as negative electrode active materials to assemble button batteries, and the specific method was as follows:
[0066] The negative electrode sheet is composed of a modified porous hard carbon negative electrode material, Super P conductive carbon, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) binder, wherein the mass ratio of the modified porous hard carbon negative electrode material, Super P, SBR and CMC is 90:2:4:4. The modified porous hard carbon negative electrode material and Super P conductive carbon are mixed evenly in proportion by grinding for 20 minutes, and the evenly mixed modified porous hard carbon negative electrode material and Super P conductive carbon are mixed with SBR (49.5% aqueous solution) and CMC (2% aqueous solution), placed on a micro ball mill and stirred for 15 minutes to obtain a uniform slurry, and the slurry is evenly coated on aluminum foil (the coating amount is 110.23g / cm 2 ), vacuum dried in an oven at 120°C for 5 hours, and punched out negative electrode sheets with a diameter of 12 mm using a gun press, which were weighed and set aside for use.
[0067] A sodium ion battery half-cell is formed by using a sodium sheet as the positive electrode, the negative electrode is the negative electrode sheet prepared above, the separator is a PP separator or a glass cellulose separator, and the electrolyte is a 1 mol / L sodium hexafluorophosphate solution. The test item density is 180 mA / g, the test voltage range is 0.05 V-2 V, and the button battery is subjected to a charge and discharge cycle test.
[0068] Figure 3 The first cycle discharge capacity comparison chart of button cells using modified porous hard carbon negative electrode materials JH-1 and JH-2 prepared in Example 1 of the present invention and Comparative Example 1 as negative electrode active materials. It can be seen from the figure that the first cycle discharge capacity of JH-1 is 353 mAhg -1 , JH-2 first effective capacity is 150mAhg -1 In comparative example 1, only acid leaching without alkali leaching was performed without adding liquid B. During calcination, the hard carbon structure could not be etched. In the absence of protective gas, carbon material could be prepared and only sodium storage contact sites could be formed on the carbon surface. Therefore, the button battery test performance was poor.
Claims
1. A method for forming pores in a modified porous hard carbon negative electrode material without protective gas, characterized in that: The method specifically comprises the following steps: (1) pre-calcining the biomass raw material under oxygen-free and negative pressure conditions to obtain a hard carbon precursor; after crushing, acid washing and water washing to neutrality to obtain a purified hard carbon precursor dispersion; (2) adding epoxy resin and starch material to the purified hard carbon precursor dispersion in order according to the ratio, mixing, and obtaining a mixed slurry A; then adding sodium hydroxide solution to the mixed slurry A according to the ratio, stirring for 1-3 hours, obtaining a mixed slurry B, and mixing by ball milling to form a mixed material; (3) spray drying the mixture, and then calcining it at 1050-1700° C. for 2-4 hours; after the calcination, cooling the obtained product to room temperature to obtain the modified porous hard carbon negative electrode material.
2. The method according to claim 1, characterized in that: The biomass raw material in step (1) is one or more of coconut shell, bamboo, hard fruit shell, straw and grass leaf.
3. The method according to claim 1, characterized in that: The pre-calcination temperature in step (1) is 600-800° C., and the pre-calcination treatment time is 3-5 hours.
4. The method according to claim 1, characterized in that: The mass ratio of the hard carbon precursor to the epoxy resin in step (2) is 100:1-8.
5. The method according to claim 1, characterized in that: The starch material in step (2) is a mixture of one or more of corn starch, potato starch, rice starch and wheat starch.
6. The method according to claim 1, characterized in that: The mass ratio of the hard carbon precursor to the starch material in step (2) is 100:8-26.
7. The method according to claim 1, characterized in that: The mass ratio of the hard carbon precursor to the sodium hydroxide in the sodium hydroxide solution in step (2) is 100:22-43.
8. The modified porous hard carbon negative electrode material prepared by the method according to any one of claims 1 to 7.
9. Application of the modified porous hard carbon negative electrode material prepared by the method according to any one of claims 1 to 7 in sodium ion batteries.
10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The active material used in the negative electrode is a modified porous hard carbon negative electrode material prepared by the method according to any one of claims 1 to 7.